2018
DOI: 10.1111/jcmm.13738
|View full text |Cite
|
Sign up to set email alerts
|

From fever to immunity: A new role for IGFBP‐6?

Abstract: Fever is a fundamental response to infection and a hallmark of inflammatory disease, which has been conserved and shaped through millions of years of natural selection. Although fever is able to stimulate both innate and adaptive immune responses, the very nature of all the molecular thermosensors, the timing and the detailed mechanisms translating a physical trigger into a fundamental biological response are incompletely understood. Here we discuss the consequence of hyperthermic stress in dendritic cells (DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 83 publications
(189 reference statements)
0
18
0
Order By: Relevance
“…This result suggests that DCs’ maturation not only depends on danger signals with HSPs but also on hyperthermia itself independently ( 61 ). Further studies proposed that fever-range hyperthermia promote DCs from a quiescent status to an activated status by promoting the metabolic reprogramming in them ( 62 , 63 ). The authors proposed that hyperthermia increased the expression of insulin-like growth factor binding protein 6 (IGFBP-6) and HSP70, whose autocrine mechanism increases the glycolysis, decreases the activity of the mitochondrial respiratory chain and consequent oxidative phosphorylation (OxPhos), enhances the production of NO and ROS, and promotes the mitochondrial Ca 2+ overload.…”
Section: Hyperthermia Enhanced the Immune Response In Multiple Stepsmentioning
confidence: 99%
“…This result suggests that DCs’ maturation not only depends on danger signals with HSPs but also on hyperthermia itself independently ( 61 ). Further studies proposed that fever-range hyperthermia promote DCs from a quiescent status to an activated status by promoting the metabolic reprogramming in them ( 62 , 63 ). The authors proposed that hyperthermia increased the expression of insulin-like growth factor binding protein 6 (IGFBP-6) and HSP70, whose autocrine mechanism increases the glycolysis, decreases the activity of the mitochondrial respiratory chain and consequent oxidative phosphorylation (OxPhos), enhances the production of NO and ROS, and promotes the mitochondrial Ca 2+ overload.…”
Section: Hyperthermia Enhanced the Immune Response In Multiple Stepsmentioning
confidence: 99%
“…Such activities are complemented and integrated by the effects given by IGFBP-6 independently on IGF-II, including regulation of proliferation, apoptosis, angiogenesis, and cell migration [2,3]. Recently, a role of IGFBP-6 in inflammatory reactions and diseases has been delineated [4]. We have shown that IGFBP-6 has chemoattractant properties toward cells of the innate (neutrophils, monocytes) and adaptive (T cells) immunity [5,6].…”
Section: Introductionmentioning
confidence: 98%
“…IGFBP-6 functions include inhibition of IGF-2 dependent cell division, migration, differentiation and survival in addition to inhibiting cell proliferation and stimulating apoptosis independently of IGF-2 [ 228 ]. IGFBP-6 also holds intracellular function through binding to nuclear and possibly mitochondrial receptors as well [ 229 ].…”
Section: Tissue Engineering and Periodontal Regenerationmentioning
confidence: 99%